Women in healthcare in Imperial Russia: The contribution of the surgeon Nikolay I Pirogov. (February 2021) - Hendriks, Inge; Zhuravloyv, Dmitry; Bovill, James; Boer, Fredrik; Hogendoorn, Pancras
Nikolay Ivanovich Pirogov, one of the greatest Russian surgeons of the 19th Century, was convinced of the importance of deploying nurses to care for the casualties of war. With the support of Grand Duchess Elena Pavlovna, sister-in-law of Tsar Nikolas I, Pirogov realised the idea during the Crimean war when Russia became the first country to send female nurses to the battle front. Later in the 19th century, large numbers of Russian women trained as nurses under the auspices of the Russian Red Cross, founded in 1867. In peacetime, their expertise was extremely valuable.